YOUNG WOMEN TRAVELERS’ INTENTION TO VISIT HALAL DESTINATION - Imelda Rahmawati Khaerudin (International Humanities and Applied Science Journal, 2022)
The purpose of this paper is to introduce the variable of Travel Motivation (TRMT), Travel Constraints (TCON), and Destination Image (DI) with Push-Pull Motivation theory to investigate Indonesian young female Muslim travelers’ intention to visit Lombok as a halal destination. Data were collected through 187 distributed questionnaires toward Indonesian young female Muslim travelers. The collected data was analyzed by using SmartPLS. Indonesian young female Muslim travelers are highly motivated for travel-related activities, specifically to obtain a level of independence and empowerment. This study only focusing on Lombok as a halal destination. Young female Muslim travelers appear as a lucrative segment; thus, Lombok should provide marketing promotion that target this segment. Further, halal destination also provides the young women Muslim travelers to express their religious beliefs, in ways that are relevant to Muslim women. The value of this study is the finding that young women Muslim travelers are eager to visit a halal destination, and appear to be capable to overcome both internal and external factors that might prohibit them to travel.